Management Sensitization to Information Use - Dasgupta, A. K. (Journal of Information and Knowledge, 1978)
Highlights the role of information in decision-making. Presents narrower and wider view of Management Information. Discusses the Management Development Programmes, the needs in Management Information, the tasks of motivating managers towards use of information. Presents some methods used in Administrative Staff College of India (ASCI) in motivating managers to use information.